1986
DOI: 10.1021/bi00351a019
|View full text |Cite
|
Sign up to set email alerts
|

Human placental estradiol 17.beta.-dehydrogenase: sequence of a histidine-bearing peptide inthe catalytic region

Abstract: The amino acid sequence of an octapeptide from the catalytic site of human placental estradiol 17 beta-dehydrogenase (EC 1.1.1.62) was established by affinity-labeling techniques. The enzyme was inactivated separately by 12 beta-hydroxy-4-estrene-3,17-dione 12-(bromo[2-14C]acetate) and 3-methoxyestriol 16-(bromo[2-14C]acetate) at pH 6.3. The inactivations, in both cases, followed pseudo-first-order kinetics with half-times for the 12 beta and 16 alpha derivatives being 192 and 68 h, respectively. Both derivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 13 publications
3
17
0
Order By: Relevance
“…It was found that the 17-ketone was in close proximity with the C4 position of the nicotinamide ring, and that the phenolic hydroxyl group on the A-ring of the steroid formed a hydrogen bond with the imidazole nitrogen of His 221. Other amino acids in the cleft included His and Cys residues that were previously identified by bromoacetoxysteroid affinity-labeling studies to be involved in steroid binding (185,186). The active site also contained Tyr 155 and Lys 159 near the C17 ketone, and these residues are believed to be catalytic.…”
Section: June 1997 Molecular Endocrinology Of Hsds 295mentioning
confidence: 99%
“…It was found that the 17-ketone was in close proximity with the C4 position of the nicotinamide ring, and that the phenolic hydroxyl group on the A-ring of the steroid formed a hydrogen bond with the imidazole nitrogen of His 221. Other amino acids in the cleft included His and Cys residues that were previously identified by bromoacetoxysteroid affinity-labeling studies to be involved in steroid binding (185,186). The active site also contained Tyr 155 and Lys 159 near the C17 ketone, and these residues are believed to be catalytic.…”
Section: June 1997 Molecular Endocrinology Of Hsds 295mentioning
confidence: 99%
“…Since the 1950s (Ryan & Engel 1953), 17 -hydroxysteroid dehydrogenase/17-ketosteroid reductase (17HSD/KSR) activities have been characterized, and 17HSD/KSR enzymes have been purified from a large number of tissues of several species (see Jarabak 1969, Nicolas & Harris 1973, Bogovich & Payne 1980, Milewich et al 1985, Inano & Tamaoki 1986, Murdock et al 1986, Tait et al 1989, Martel et al 1992, Blomquist 1995. Eight enzymes named HSD types 1-8, hereafter called 17HSD/KSR1-8, have so far been cloned (see Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…His 221 , first identified by affinity labeling studies (27)(28)(29), was thought to be involved in the specific binding of the steroid. Indeed, the construction of an H221A mutant led to an enzyme displaying a higher K m and lower V max relative to the wild type (16).…”
mentioning
confidence: 99%